2008
DOI: 10.1007/s00423-008-0341-3
|View full text |Cite
|
Sign up to set email alerts
|

Extravascular perivenous fibrin support leads to aneurysmal degeneration and intimal hyperplasia in arterialized vein grafts in the rat

Abstract: Background and aims External support of vein grafts by fibrin glue possibly prevents overdistension, vascular remodeling, and neointimal hyperplasia. Previous animal models of neointimal hyperplasia showed conflicting results. Here, long-term effects of external fibrin glue support were studied in a new rat model of jugular vein to abdominal aorta transposition. Materials and methods and methods In male Wistar rats (250-300 g) right jugular vein (1.0-1.5 cm) was transposed to the infrarenal aorta. Fibrin glue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
(23 reference statements)
0
2
0
7
Order By: Relevance
“…Experimental data have shown that the application of fibrin glue on the external surface of vein grafts lead to aneurysmal degeneration and excessive intimal hyperplasia which may have jeopardized vein graft patency [17][18]. Recent clinical data showed that suturing and fixating an external support device to the anastomoses leads to early failure of vein grafts, most probably due to an acute constriction of the anastomosis site [15].…”
Section: Resultsmentioning
confidence: 99%
“…Experimental data have shown that the application of fibrin glue on the external surface of vein grafts lead to aneurysmal degeneration and excessive intimal hyperplasia which may have jeopardized vein graft patency [17][18]. Recent clinical data showed that suturing and fixating an external support device to the anastomoses leads to early failure of vein grafts, most probably due to an acute constriction of the anastomosis site [15].…”
Section: Resultsmentioning
confidence: 99%
“…This effect is associated with maintenance of blood vessel endothelium integrity, inhibition of PCNA expression, facilitation of smooth muscle cell migration, and formation of a new vascular network (Wan et al, 2006a,b). However, the long-term consequences are disputed (Stojanovic et al, 2009); therefore, attention must be given to the mechanism underlying restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Grafik 1: (Stojanovic et al 2009) Kontrollgruppe: Venentransposition ohne Anwendung von Fibrinkleber (schwarze Säulen) vs. Fibrinkleber-Gruppe: Venentransposition mit Anwendung von Fibrinkleber (weiße Säulen).…”
Section: Intimale Flächeunclassified
“…Intimafläche (µm 2 ) 2517166±356 p < 0,05 18424000±493 p < 0,05 Grafik 2: (Stojanovic et al 2009) Totale Wanddicke (μm) gemessen in der Kontrollgruppe (weiße Säulen) und in der Fibrinkleber-Gruppe (schwarze Säulen). Kontrollgruppe: Venentransposition ohne Anwendung von Fibrinkleber (weiße Säulen) Fibrinkleber-Gruppe: Venentransposition mit Anwendung von Fibrinkleber (schwarze Säulen).…”
Section: Ergebnisse Der Messungenunclassified
See 1 more Smart Citation